Effectiveness of Using The Think Pair Share Method with The Flipaclip Application Media in Learning to Write Anecdote Texts - Nurillah Shalihatul Mubarokah; Wikanengsih Wikanengsih (FKIP - Universitas Riau, 2026)
The importance of anecdotal text writing skills in Indonesian language learning to develop students’ creativity, critical thinking, and language competence. However, students often experience difficulties in expressing ideas coherently and creatively due to monotonous teaching methods and limited use of instructional media. This study aims to examine the effectiveness of the Think Pair Share (TPS) method assisted by the FlipaClip application in learning to write anecdotal texts. The research employed a quasi-experimental design with a non-equivalent control group involving two classes of tenth-grade students at SMK Yadika Sumedang. The experimental class was taught using the TPS method integrated with FlipaClip media, while the control class applied the TPS method without media assistance. Data were collected through pre-test and post-test writing assessments and analyzed using descriptive statistics and inferential tests. The results show that students taught using the TPS method assisted by FlipaClip achieved higher improvement in anecdotal text writing ability compared to students in the control class. The integration of cooperative learning and digital animation media enhanced students’ engagement, creativity, and learning outcomes. It can be concluded that the Think Pair Share method assisted by the FlipaClip application is effective in improving students’ anecdotal text writing skills.